Semi-permanent expandable hydropower system for river applications in Malaysia - Hazmin, Mohd Haniff (2021)
This thesis consists of research regarding a new system of harnessing hydropower energy that utilises product development process methodology, computer-aided drawing software, and computational fluid analysis software as the platforms to conduct fluid dynamic analysis on the product development. The objectives of this research is to develop an alternative hydropower harnessing method for Malaysian river applications. In this research, a working prototype for the generator unit that will be used in the new method is developed. The product development process includes doing prior research, information gathering, concept generation and evaluation of the concepts via a qualitative concept selection process. The main parts of the prototype are designed using CATIA version 5.2, analysed using ANSYS version 16.0, manufactured via 3D printing and the 3D printed turbines field tested in local rivers. The product development process resulted in concept 2 being chosen to be developed further. From the ANSYS analysis, experimental and field test data, turbine runner with curved blades proved to perform better than straight blades at an average of 41% difference. Further ANSYS analysis done on generator arrangement shows that the turbines will perform at a maximum efficiency roughly around the value of X, Y and Z at 500 cm. The results shows that the prototype has a good potential to be able to generate power while operating in a relatively small site. The new method also possesses the characteristics to be less environmentally intrusive than the conventional hydropower method, with significantly less assumed costs due to its operating size and easier maintenance. This research will be able to contribute towards powering areas with constant flowing rivers, especially isolated areas where common power grid cannot access. To conclude the project, a further recommendation for future works is proposed to perfect the system and improve its efficiency and practicality.